DEVELOPMENT OF SINGKAWANG CITY AS A GASTRONOMY TOURISM DESTINATION IN WEST KALIMANTAN - Christianto, Jery; Made Gede Darma Susila, I (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2025)
Singkawang City is one of the potential tourism destinations that is suitable to be developed as a gastronomy tourism destination. This is due to the diversity of tourism destinations and tourism facilities in the city. The purpose of this study is the extent of the development of Singkawang City as a tourism destination and to find out the direction of city development as a gastronomy tourism destination. The research was conducted with a qualitative descriptive approach with data collection techniques such as observation and literature study. The results of this study obtained that this city has arranged well its tourism destinations, it can be seen that road access, supporting facilities and infrastructure, tourist attractions and institutions contained therein. In addition, in terms of gastronomic development, Singkawang City is suitable to be developed as a gastronomy tourism destination, this can be seen in the typical culinary served and diverse. Keywords: tourism development, gastronomy, tourism destination